Evaluation of the Bangor Dyslexia Test (BDT) for use with Adults. (8th January 2016) - Reynolds, Andrea Elaine; Caravolas, Markéta
Abstract : The Bangor Dyslexia Test (BDT) is a short, easy‐to‐administer screener for use with a broad age range, which has been in use in the UK for over three decades. A distinctive feature of the battery is its focus on skills requiring aspects of verbal and phonological processing without, however, measuring literacy skills per se. Despite its longstanding existence and usage, there has been no evaluation of the psychometric properties of the battery as an adult dyslexia screener. We examined the psychometric properties of the BDT and evaluated its capacity to discriminate between adults with and without dyslexia. A large archival sample of university students with dyslexia ( n = 193) and students with no reported literacy difficulties ( n = 40) were compared on the BDT as well as on literacy and cognitive measures. Statistical analyses revealed the BDT to be a reliable ( α = .72) and valid dyslexia screening tool with the capacity to effectively identify adults at risk of the disorder with an overall classification rate of 94% (sensitivity 96.4% and specificity 82.5%). In addition, higher indices of dyslexia risk on the BDT were associated with lower scores on standardized measures of literacy. Copyright © 2016 John Wiley & Sons, Ltd.